Diagnostics of Arterial Hypertension in Adolescents Based on Analysis of Daily BP Rpofile and Vascular Wall Rigidity - M. Y. Ledyaev; L. V. Svetlova; V. B. Zukova; Y. A. Ananieva (Медицинский вестник Юга России, 2011)
Purpose: The possibility of using parameters characterizing arteriole tone obtained from daily monitoring of BP in teenage children.Materials and Methods: In the present study we used a bifunctional ECG and BP monitoring device MnSDP-3. This device permits determining basic haemodynamic parameters as well as PTT (pulse transit time) and dpdt. We also performed estimation of arteriole tone (AT). Patients were divided into two groups. The first group included 30 teenagers with verified essential arterial hypertension. The second, control group, included 30 teenagers of health group I and II with BP varying from 5 to 89 percentile.Results: Mean daily PTT value in the first group amounted to 141.3 + 9.3 ms, while in the control group – 144.4 + 9.72 ms. Mean dp/dt values for a day amounted to 906.1 + 168.0 mm Hg in the first teenager group, while in the control group – 677.4 + 107.4 mm Hg. Mean AT values for a day in the first group were 42.1 + 10.9 mm Hg, while in the control group they amounted to 32.3 + 7.5 mm Hg.Summary: Such parameters as dp/dt and arteriole tone are most informative for early diagnostics of arterial hypertension.